1996
DOI: 10.1063/1.362797
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of chemically deposited CdSe nanocrystallites: Effects of crystallite polydispersity

Abstract: CdSe nanocrystalline films were prepared by chemical solution deposition. Photoluminescence (PL) spectroscopy was utilized to characterize the prepared films. We observed that the PL peak position of the films gradually shifts from ∼595 to ∼670 nm as the deposition time increases. Also, the PL spectra become broadened with the increase of deposition time. The data indicate that as the deposition time increases, the crystal size increases; but once the crystal size reaches a critical volume, crystal growth term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…W structural change, in this last case, is related with the minimum in the E g versus T a plot [10]. The good concordance between theory and experiment by employing EMA in CdSe for large R values is well known [22]. 4, two mechanisms contribute to the E g versus T d behavior.…”
Section: Resultssupporting
confidence: 52%
“…W structural change, in this last case, is related with the minimum in the E g versus T a plot [10]. The good concordance between theory and experiment by employing EMA in CdSe for large R values is well known [22]. 4, two mechanisms contribute to the E g versus T d behavior.…”
Section: Resultssupporting
confidence: 52%
“…Figure 3 shows the room temperature photoluminescence spectrum of the 7-nm diameter CdSe crystallites and compares it with its excitation spectrum. The PL spectrum consists of one sharp emission feature at 600 nm, which has an obvious blue shift compared with that of bulk materials (10,11), indicating its quantum con"nement. The sharp emission feature suggests the highly monodisperse samples.…”
Section: Resultsmentioning
confidence: 99%
“…However we have previously reported that crystallite-size dependence of the transport and phototransport properties in solid-state ensembles of semiconductor quantum dots by finding a Meyer-Neldel-like behaviour for the former and by comparing the experimental results with computer simulations for the latter showed that the aforementioned evidence were associated with the quantum confined induced variation of the bandgap in the individual dots [22]. CBD of the films is known to occur in two steps, first of which is nucleation and the second is growth [33]. As soon as we dip the slide in the chemical bath, centers of nucleation are formed on the surface of the slide, and with time the cluster growth on these centers of nucleation takes place at the same time new centers of nucleation are created on surface of the slide.…”
Section: Resultsmentioning
confidence: 99%